Reconstruction Of The Concept Of A Foundation As A Non Profit Oriented Legal Entity - Subesar, Haris (PDIH Untag Semarang, 2024)
This research is to find alternative solutions to the many cases of abuse of legal entities in the form of foundations in Indonesia. Foundations as non-profit oriented legal entities have so far been misused to carry out money laundering and other criminal acts, even though the purpose of the Foundation is aimed at social, religious and educational activities. This research is a normative juridical research based on the approach to the laws and regulations in force in Indonesia. This research utilizes primary data sources and secondary data sources. The secondary data comprises primary legal materials and secondary legal materials, which are then analyzed and presented qualitatively. The research results show that the law governing foundations in Indonesia currently, namely Law number 28 of 2004 as an amendment to Law Number 16 of 2001. The last amendment to the Foundation Law was made in 2004, so it has been quite a long time and it is time for changes to be made by reconstructing the current Foundation Law to better guarantee legal certainty for for foundations in Indonesia. Based on the discussion above, several provisions need to be strengthened to address the potential misuse of foundations for money laundering activities. Additionally, from a structural perspective, there is a need for reinforcing oversight mechanisms and intensifying public education efforts